2022
DOI: 10.1111/geb.13598
|View full text |Cite|
|
Sign up to set email alerts
|

A global analysis of viviparity in squamates highlights its prevalence in cold climates

Abstract: Aim: Viviparity has evolved more times in squamates than in any other vertebrate group; therefore, squamates offer an excellent model system in which to study the patterns, drivers and implications of reproductive mode evolution. Based on current species distributions, we examined three selective forces hypothesized to drive the evolution of squamate viviparity (cold climate, variable climate and hypoxic conditions) and tested whether viviparity is associated with larger body size.Location: Global. Time period… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 117 publications
0
28
0
Order By: Relevance
“…less frequent reproduction) and has been weakly linked to threatened extinction risk in Australian squamates (Senior et al., 2021). Additionally, viviparity is posited to be a cold climate adaptation (Zimin et al., 2022) and thus species often have a restricted, high elevation range and inhabit areas where climate change is having a rapid impact (Senior et al., 2021; Sinervo et al., 2010). Cold climates are often subjected to a sizable human footprint in Australia which negatively impacts species due to an association with habitat loss, overexploitation and invasive species (Senior et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…less frequent reproduction) and has been weakly linked to threatened extinction risk in Australian squamates (Senior et al., 2021). Additionally, viviparity is posited to be a cold climate adaptation (Zimin et al., 2022) and thus species often have a restricted, high elevation range and inhabit areas where climate change is having a rapid impact (Senior et al., 2021; Sinervo et al., 2010). Cold climates are often subjected to a sizable human footprint in Australia which negatively impacts species due to an association with habitat loss, overexploitation and invasive species (Senior et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…widespread species, Horváthová et al, 2013; Liang et al, 2018; Liang & Shi, 2017; Pincheira‐Donoso & Meiri, 2013) and further affect interspecific variation of body size at different altitudes. Besides, life‐history traits could influence body size, for example, viviparity is associated with large body size but always existed in cold regions (Zimin et al, 2022). At the high‐altitude stage of this study, viviparous Phrynocephalus lizards were found to inhabit extremely high regions with enlarged size, which could buffer the overall trends of body size variation along altitudes.…”
Section: Discussionmentioning
confidence: 99%
“…2016). In reptiles, viviparity developed as an adaptation to increase reproduction success in cold climates (Zimin et al . 2022), and might also confer species with the ability to buffer populations against environmental stochasticity, including resilience to disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…Recently reported links between demographic buffering and transient dynamics after disturbances (demographic resilience) (Capdevila et al 2020) may explain these patterns (Stott et al 2010;McDonald et al 2016). In reptiles, viviparity developed as an adaptation to increase reproduction success in cold climates (Zimin et al 2022), and might also confer species with the ability to buffer populations against environmental stochasticity, including resilience to disturbances. Therefore, demographically buffering species may outcompete others in the most extreme fire regimes (total absence of fire vs. frequent and severe fires), as we show here.…”
Section: Discussionmentioning
confidence: 99%